Level of Inhibition in Trained Secondary School Teachers: Evidence from Pakistan - Fauzia Rafiq; Yousuf Sharjeel (Journal of Education and Educational Development, 2020)
The study found that the inhibition amongst trained secondary school teachers in using learned teaching methodologies is caused due to the lack of content knowledge, insufficient support from the administration, scarce continuous professional development opportunities, unsupportive environment, large class size, in-efficiency to integrate technology, inadequate post-training support and lack of motivation. The study also concluded that teaching inhibition is not possible to be controlled by virtue of teacher’s training skills only. This study recommends that trained teachers be permitted to experiment within their permissible limits to try new teaching methodologies under supervised conditions and reflect upon them intermittently. Continuous support of the school administration is the key to successfully implementing the newly-acquired pedagogic and scholastic skills for an educational institution to improve its teacher education programme.
Keywords: Teacher inhibition; prospective teachers; learned methodologies; professional development